2003
DOI: 10.1023/a:1021119112927
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Prophylactic transient hypoxia (preconditioning) increased neuron resistance to subsequent induction of severe hypoxia. Published data and results obtained by the authors on the molecular-cellular mechanisms of hypoxic preconditioning are presented. The roles of intracellular signal transduction, genome function, stress proteins, and neuromodulatory peptides in this process are discussed. The roles of glutamatergic as well as calcium and phosphoinositide regulatory systems and neuromodulatory factors as compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In vitro models of cerebral hypoxic preconditioning include studies in hippocampal slices (Pérez-Pinzón et al, 1996 ; Bickler and Fahlman, 2009 ) and olfactory cortex (Semenov et al, 2002 ; Samoilov et al, 2003 ), as well as primary neuronal cultures (Arthur et al, 2004 ). It has been demonstrated that preconditioning with a single short (2 min) episode of anoxia in slices of the olfactory cortex or three trials of 1 min anoxia in the hippocampal slicesincreases the resistance of the cells to severe “test” anoxia, preventing depression of the evoked potential amplitudes and calcium overload associated with anoxic injury whereas moderate calcium load is required for induction of tolerance during anoxic preconditioning (Pérez-Pinzón et al, 1999 ; Semenov et al, 2012 ).…”
Section: Hypoxic Preconditioningmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro models of cerebral hypoxic preconditioning include studies in hippocampal slices (Pérez-Pinzón et al, 1996 ; Bickler and Fahlman, 2009 ) and olfactory cortex (Semenov et al, 2002 ; Samoilov et al, 2003 ), as well as primary neuronal cultures (Arthur et al, 2004 ). It has been demonstrated that preconditioning with a single short (2 min) episode of anoxia in slices of the olfactory cortex or three trials of 1 min anoxia in the hippocampal slicesincreases the resistance of the cells to severe “test” anoxia, preventing depression of the evoked potential amplitudes and calcium overload associated with anoxic injury whereas moderate calcium load is required for induction of tolerance during anoxic preconditioning (Pérez-Pinzón et al, 1999 ; Semenov et al, 2012 ).…”
Section: Hypoxic Preconditioningmentioning
confidence: 99%
“…A central place in the studies of hypoxic preconditioning belongs to identification of its molecular mechanisms with special attention being paid both to their unique character and similarity with the mechanisms of ischemic preconditioning. The process of preconditioning can be divided into several phases starting with the phase of initiation of hypoxic tolerance (Samoilov, 1997 ; Samoilov et al, 2003 ) or the immediate phase of adaptation to hypoxia (Lukyanova et al, 2013 ) which covers the first few minutes following the exposure to moderate hypoxia. This acute stage is clearly linked with the launch of several molecular signaling processes.…”
Section: Cerebral Mechanisms Of Hypoxic Preconditioningmentioning
confidence: 99%
See 2 more Smart Citations